2020
DOI: 10.1016/j.ssci.2019.104535
|View full text |Cite
|
Sign up to set email alerts
|

An industry structured for unsafety? An exploration of the cost-safety conundrum in construction project delivery

Abstract: An industry structured for unsafety? An exploration of the cost-safety conundrum in construction project deliveryConstruction accidents can have major social, financial, reputational and legal implications. Hence, it is to be expected that safety is often presented as a key priority for construction organisations. However, existing evidence suggests that within the construction industry, safety often loses the battle when a trade-off is required with project cost. Improved understanding of the manifestations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 74 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…The graph shows the different levels of preventive action control: L cap > 60% exhaustive control, L cap > 36% intensive control, L cap > 20% greater control, L cap > 12% more control, L cap > 4% adequate control and L cap < 4% optimal control. It can be verified that exhaustive levels of control are required for the construction systems that imply greater risk in accidents: foundations, structures, floors, façades, and roofs [ 39 , 50 , 51 ]. The risk perception values for the workers were between 10 and 15.…”
Section: Results and Discussion Participationmentioning
confidence: 99%
“…The graph shows the different levels of preventive action control: L cap > 60% exhaustive control, L cap > 36% intensive control, L cap > 20% greater control, L cap > 12% more control, L cap > 4% adequate control and L cap < 4% optimal control. It can be verified that exhaustive levels of control are required for the construction systems that imply greater risk in accidents: foundations, structures, floors, façades, and roofs [ 39 , 50 , 51 ]. The risk perception values for the workers were between 10 and 15.…”
Section: Results and Discussion Participationmentioning
confidence: 99%
“…Han et al proposed that increases in tangible safety investment (e.g., incentive) generated stronger motivations for employees to enhance their behavioral safety performance [ 34 ]. Oswald et al suggested that the construction industry should invest more in safety and forward-thinking companies should exceed the minimum standards required by safety regulations and invest in voluntary accident prevention costs [ 14 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Safety investment usually has significant effects on the overall budget of a project [ 14 ]. Therefore, the optimal safety investment level ought to strike a balance between reducing the accident rate and controlling total costs [ 15 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations